PENERAPAN STRATEGI PEMBELAJARAN AKTIF INDEX CARD MATCH UNTUK MENINGKATKAN HASIL BELAJAR - Hanifah, Nurul Alif; Hanifah, Nurdinah; Isrok'atun, Isrok'atun (Jurnal Pena Ilmiah, 2017)
According to the result of observation toward the V grade student of Karangpawulang Elementary School, shows the study result of History Character in Hindu, Budha and Islam era Material is still under KKM, 70. In the research used Index Card Match Active Learning Strategy for increase the process and result of study. The research uses PTK methods, and the research design refers to Kemmis and Taggart that consists of planning, tinfakan, observation and reflection. As for the observation instrument that used are guidelines observation, interview,Â  field notes, and student study result. According to the research that has done, it can be concluded that the application of Index Card Match Active Learning Strategy can increase the student study result of History Character in Hindu, Budha and Islam era Material. That is proven by the attainment result target, 90% of total student reach KKM, 95% of student Declared complete in that learning.